2005
DOI: 10.1007/s00168-004-0224-7
|View full text |Cite
|
Sign up to set email alerts
|

Income convergence across Canadian provinces in the 20th century: Almost but not quite there

Abstract: C32, O40, R10,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…We have provided additional information to explain the differences in the prevalence of self-reported CB between educational attainment, household income and smoking status according to location of residence (Table 2). Previous studies have also reported such variations across Canada (11)(12)(13)(14)(15)(16). The regional variation in these factors may contribute to the differences in the prevalence of self-reported CB.…”
Section: Discussionmentioning
confidence: 80%
“…We have provided additional information to explain the differences in the prevalence of self-reported CB between educational attainment, household income and smoking status according to location of residence (Table 2). Previous studies have also reported such variations across Canada (11)(12)(13)(14)(15)(16). The regional variation in these factors may contribute to the differences in the prevalence of self-reported CB.…”
Section: Discussionmentioning
confidence: 80%
“…SeeDeJuan and Tomljanovich (2005),Barrios and de Lucio (2003), andCarlino and Sill (2001) for a review of recent work in this area.…”
mentioning
confidence: 99%
“…What differentiates these Canadian studies is the set of determinants used to explain regional growth rates. Among the determinants analyzed were governmental redistribution programs (Coulombe ; DeJuan and Tomljanovich ), urbanization (Coulombe , ; Coulombe and Tremblay ), migration (Helliwell ; Lee ), human capital (Coulombe ; Coulombe and Tremblay , ; Coulombe, Tremblay, and Marchand ; Lee ), and trade (Coulombe ). In contrast to our study, none of these Canadian studies have considered entrepreneurship as a determinant of regional growth or its dynamic impact on growth.…”
Section: Literaturementioning
confidence: 99%